Assessment of Groundwater Pollution in Erode City (North), Tamil Nadu, India - T. Pradeep; V. Sampathkumar (Current Approaches in Science and Technology Research Vol. 1, 2021)
Water is a very important element on the earth for life to exist. Humans have long relied on water as a life source, and all organisms require it to survive. Our research area is on the North Erode City of TamilNadu. Many dyeing industries, chemical industries, and tanneries surround Erode north. These industries release their effluents directly into the groundwater sources, and get polluted. The groundwater is greatly polluted due to waste disposal by tannery industries, dyeing units and paper mills situated near by the river basin. In our project, we conducted a systematic investigation to assess water pollution and the effects of effluents discharged by industry. We collected 20 ground water samples in the erode region, and the water quality was assessed using quality parameters such as temperature, pH, EC, chlorides, alkalinity, total hardness, total dissolved solids, total solids, suspended solids, DO, and COD. Due to the impact of dyeing industries, tanneries, and chemical industries, the results of a few samples were found to be highly polluted.As a result, maintaining the quality of ground water in this area is essential for long-term sustainability.